Design and fabricate back suspension system for go-kart - Mohd Bakeri, Muhammad Syafiq; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The design and development of a go-kart rear suspension system play a crucial role in enhancing stability, traction, and ride comfort. This project aimed to create a functional and durable suspension system by integrating key components such as shock absorbers, coil springs, brackets, and a back frame. Three existing designs were benchmarked to evaluate their strengths and weaknesses, leading to an optimized system that could handle various terrains and driving conditions. The fabrication process involved material selection, cutting, sanding, drilling, welding, and assembly, ensuring structural integrity and precision. Shielded Metal Arc Welding (SMAW) was initially used but later replaced with Tungsten Inert Gas (TIG) welding for better material compatibility. Rigorous testing confirmed that the suspension system provided improved handling, reduced vibrations, and enhanced ride quality. The results demonstrated that the developed suspension system met performance, durability, and safety standards. The final prototype ensured smooth driving dynamics, better weight distribution, and optimal shock absorption. This study provides valuable insights for further adjustability, maintenance, and customization improvements to enhance go-kart performance. The successful implementation of this project highlights the practicality and effectiveness of a well designed rear suspension system in go-kart engineering.